2020
DOI: 10.3389/fpsyg.2020.00821
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Work-Related Rumination and Executive Function Using the Behavior Rating Inventory of Executive Function

Abstract: Work-related rumination has been associated with a number of health complaints, however, little is known about the underlying factors associated with rumination. Previous work using proxy measures of executive function showed work-related rumination to be negatively associated with executive function. In this paper, we report two studies that examined the association between work-related rumination and executive function utilizing an ecological valid measure of executive function: the Behavior Rating Inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
(76 reference statements)
1
15
0
1
Order By: Relevance
“…For instance, it was found that psychological detachment was related to better patient and worker safety (Buljac-Samardžić et al, 2018;Chen and Li, 2020), lower counterproductive work behavior (Chen et al, 2017), and better work-life balance (Barber et al, 2019). Considering the different types of work-related thoughts during nonwork time, studies have, for instance, investigated relationships to work-family-conflict and enrichment (Junker et al, 2020), executive functions (Cropley and Collis, 2020;Cropley et al, 2016), and thriving (Weigelt et al, 2019).…”
Section: Empirical Findingsmentioning
confidence: 99%
“…For instance, it was found that psychological detachment was related to better patient and worker safety (Buljac-Samardžić et al, 2018;Chen and Li, 2020), lower counterproductive work behavior (Chen et al, 2017), and better work-life balance (Barber et al, 2019). Considering the different types of work-related thoughts during nonwork time, studies have, for instance, investigated relationships to work-family-conflict and enrichment (Junker et al, 2020), executive functions (Cropley and Collis, 2020;Cropley et al, 2016), and thriving (Weigelt et al, 2019).…”
Section: Empirical Findingsmentioning
confidence: 99%
“…Not surprisingly, we found an effect of work-related rumination on cognitive failures on the next day; these results indicate impaired behavioral regulation. Work-related rumination is known to impair executive function, especially for switching attention, thinking about different solutions, or dealing with and accepting change (Cropley & Collis, 2020). However, WHC and rumination contribute independently to the cognitive failures the next day.…”
Section: Additional Analysesmentioning
confidence: 99%
“…Interestingly, of the 25 studies revised, only seven studies used the complete WRRS and those included the original study in which the WRRS was developed ( Cropley et al, 2012 ; Querstret and Cropley, 2012 ; Vandevala et al, 2017 ; Dunn and Sensky, 2018 ; Sulak Akyüz and Sulak, 2019 ; Weigelt et al, 2019a ; Mullen et al, 2020 ), 11 used the affective and problem-solving pondering subscales ( Bisht, 2017 ; Kinnunen et al, 2017 , 2019 ; Querstret et al, 2017 ; Syrek et al, 2017 ; Vahle-Hinz et al, 2017 ; Firoozabadi et al, 2018a , b ; Junker et al, 2020 ; Zhang et al, 2020 ; Pauli and Lang, 2021 ), two studies used the problem-solving pondering and Detachment subscales ( Zoupanou et al, 2013 ; Mehmood and Hamstra, 2021 ), only one used the Detachment subscale ( Svetieva et al, 2017 ), and four studies used the affective rumination subscale ( Querstret et al, 2016 ; Van Laethem et al, 2019 ; Weigelt et al, 2019b ; Cropley and Collis, 2020 ; Smyth et al, 2020 ). Thus, the use of the subscales of the WRRS vary according to the researchers need and purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding of method of factorial designs, one used exploratory factor analysis (EFA; Cropley et al, 2012 ), seven studies used CFA ( Bisht, 2017 ; Syrek et al, 2017 ; Vahle-Hinz et al, 2017 ; Firoozabadi et al, 2018a ; Kinnunen et al, 2019 ; Sulak Akyüz and Sulak, 2019 ; Weigelt et al, 2019a , b ; and two of the studies did not report any of such methods, Querstret et al, 2016 ; Cropley and Collis, 2020 ). Those seven studies that relied on CFA, two studies used the maximum likelihood (ML) estimator, two used robust maximum likelihood (MLR), one used diagonally-weight least squares (DWLS), and two did not report it.…”
Section: Introductionmentioning
confidence: 99%